VIRTUALISASI TUHAN: Menyelak Ownership Tokoh Agama - Elia Tambunan; Simon Simon (Sekolah Tinggi Teologi Anugrah Indonesia, 2022)
The boom of information, communication and technology is changing the landscape of religious performance, especially when the West falls into a workaholicism without losing spiritualism by not leaving work. Moreover, when the world is hit by the Covid-19 pandemic, that performance is increasingly finding momentum in the virtual space. Islamic and Christian leaders are required to exist in shepherding faith of their people. Using modern socio-religious studies, religious phenomena in the digital space are analyzed in this paper to nark the virtualization of religious actorship. The data is collected from an integration of literature and social media related to the teachings of Islamic and Christian religious figures. From there, it was found, because of the sophistication of digital technology, religion in the virtual industry is trapped as a content commodity that has succeeded in placing religious figures as central actors, but often away from the supervision and control of the audience. The virtualization of religion places the religious leader as filmmakers as well as the main actors in their sacred duties but also turns towards ownership in many ways. This is revealed from the theoretical framework, namely the spiritual market, which is used here.ABSTRAKDentuman teknologi mengubah lanskap performa agama, khususnya ketika dunia Barat gila kerja tanpa kehilangan spiritualisme dengan tidak meninggalkan pekerjaan. Banyak agamawan tidak siap, tetapi banyak juga yang merekayasa diri, terlebih ketika dunia dihantam pandemic Covid-19, performa tersebut semakin menemukan momentum di ruang virtual. Pemimpin Islam dan Kristen dituntut eksis untuk menggembalakan iman umat. Lewat studi sosial keagamaan modern, fenomena keagamaan di ruang digital dianalisis dalam tulisan ini untuk menyelak virtualisasi pemeranan tokoh agama. Data dikumpulkan dari perpaduan literatur dan media sosial terkait dengan ajaran tokoh agama Islam dan Kristen. Dari sana ditemukan, oleh karena kecanggihan teknologi digital, agama dalam industri virtual terperangkap sebagai komoditas konten yang berhasil menempatkan tokoh agama sebagai aktor sentral, namun sering luput dari kontrol audiens. Secara baru, virtualisasi agama menempatkan para tokoh agama menjadi sineas sekaligus pemeran utama dalam tugas-tugas kudus mereka namun juga berkelok ke arah kepemilikan dalam banyak hal. Hal itu terungkap dari kerangka teori, yaitu pasar rohani dalam studi sosial keagamaan, yang digunakan di sini. Kata kunci: Aktor Agama, Kepemilikan, Pasar Rohani, Virtualisasi Tuhan